DNA strand transfer catalyzed by vaccinia topoisomerase: ligation of DNAs containing a 3′ mononucleotide overhang - Cheng, Chonghui (Oxford University Press, 2000)
The specificity of vaccinia topoisomerase for transesterification to DNA at the sequence 5′-CCCTT and its versatility in strand transfer have illuminated the recombinogenic properties of type IB topoisomerases and spawned topoisomerase-based strategies for DNA cloning. Here we characterize a pathway of topoisomerase-mediated DNA ligation in which enzyme bound covalently to a CCCTT end with an unpaired +1T nucleotide rapidly and efficiently joins the CCCTT strand to a duplex DNA containing a 3′ A overhang. The joining reaction occurs with high efficiency, albeit slowly, to duplex DNAs containing 3′ G, T or C overhangs. Strand transfer can be restricted to the correctly paired 3′ A overhang by including 0.5 M NaCl in the ligation reaction mixture. The effects of base mismatches and increased ionic strength on the rates of 3′ overhang ligation provide a quantitative picture of the relative contributions of +1 T:A base pairing and electrostatic interactions downstream of the scissile phosphate to the productive binding of an unlinked acceptor DNA to the active site. The results clarify the biochemistry underlying topoisomerase-cloning of PCR products with non-templated 3′ overhangs.